Cardiovascular screening of Olympic athletes reported by chief medical officers of the Rio 2016 Olympic Games - Toresdahl, B. G.; Asif, I. M.; Rodeo, S. A.; Ling, D. I.; Chang, C. J. (British Journal of Sports Medicine, 2018)
Objective: The IOC recommends periodic cardiovascular screening of athletes, but the adoption of these recommendations is unknown. The purpose of this investigation was to evaluate and compare cardiovascular screening practices of countries participating in the Rio 2016 Olympic Games.